Women in the Middle East and North Africa Change and Continuity - Haghighat-Sordellini, E. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2010)
This book explores the complexity of women's social status in the Middle East and North African region and fills a gap in the existing literature by providing an up-to-date and comprehensive portrait of women's status from a theoretical and socio-demographic perspective.